Zastosowanie Czujników Piezoelektrycznych z Tytanianu Baru do Pomiaru Szybkozmiennych Ciśnień w Rurze Uderzeniowej - Pietrzyk, Z.A.; Walenta, Z.A. (Engineering Transactions, 1964)
Two problems are discussed, both of them being connected with practical application of piezo-electric indicators to the measurement of rapidly varying pressures. The influence of vibration of the indicator on the measurement of pressure is discussed as well as methods for avoiding or reducing of the harmful influence of housing vibration on the measured quantity. The paper contains also a description of the design, characteristics and calibration of the indicators. In addition to the experimental part the paper contains some theoretical relationships for piezo- electric indicators, those of barium titaniate in particular.